Jesus' affection towards children and Matthew's tale of two kings - A. G. van Aarde (Acta Theologica)
On account of multiple and independent attestations in early Christian literature Jesus’ affection towards children can be taken as historical authentic. From a perspective of the social stratification of first-century Herodian Palestine, this article argues that it is possible to consider these children as part of the expendable class. Neither Mark nor its parallel texts in the other Gospels refer to parents bringing these children to Jesus. They seem to be “street urchins”. In this article the episode where Jesus defends the cause of fatherless children in the Synoptic Gospels is interpreted from the perspective of Matthew’s version of Jesus’ affection towards children. The aim is to demonstrate that Matthew situates the beginning and end of Jesus’ public ministry within the context of Jesus’ relationship to children. Jesus’ baptism by John (Mt 3:15) and Jesus’ entry into Jerusalem (Mt 21:1-17) form the two poles of his ministry in Matthew. Both episodes are described as a kind of “cleansing of the temple”. Both incidents were (in a midrash fashion) understood by  Matthew as fulfilment of Scripture. The baptism scene is a Matthean allusion to Isaiah 1:13-17 and the record of the entry into Jerusalem is an explicit interpretation of Jeremiah 7:1-8.